ผลของสีวัสดุห่อผลต่อคุณภาพผลมะยงชิดพันธุ์ทูลเกล้า - บุญวงศ์, ถิรวุธ; ชุมภูคำ, เจนจิรา; ยัพวัฒนพันธ์, ชินวัฒน์ (Thai Journal of Science and Technology, 2017)
บทคัดย่อ การห่อผลมะยงชิดพันธุ์ทูลเกล้าหลังดอกบาน 30 วัน ด้วยถุงพลาสติก สีดำ สีแดง สีเขียว สีขาว สีฟ้าและสีเหลือง เปรียบเทียบกับที่ไม่ห่อผล (ชุดควบคุม) เพื่อศึกษาผลของสีวัสดุห่อผลต่อคุณภาพของมะยงชิดพันธุ์ทูลเกล้า โดยเก็บเกี่ยวผลผลิตมะยงชิดที่อายุ 70 วัน หลังดอกบาน พบว่าผลมะยงชิดที่รับการห่อผลด้วยถุงพลาสติกสีต่าง ๆ มีน้ำหนักผล ปริมาตรผล ความกว้างและความยาวผลเพิ่มขึ้นเมื่อเปรียบเทียบกับการไม่ห่อผลอย่างมีนัยสำคัญทางสถิติ ผลที่ห่อด้วยถุงพลาสติกสีฟ้ามีความแน่นเนื้อผลมากที่สุด ผลที่ห่อด้วยถุงพลาสติกสีดำมีค่า TSS และมีอัตราส่วนของ TSS/TA สูงที่สุด ผลที่ห่อด้วยถุงพลาสติกสีเขียวมีค่า TA ต่ำที่สุด สีเปลือกผลมะยงชิดที่ห่อด้วยถุงพลาสติกสีเหลืองมีค่าความสว่าง (L*) และค่าสีแดง (a*) มากที่สุด ดังนั้นการห่อผลในระยะการพัฒนาผลบนต้นสามารถเพิ่มคุณภาพของผลผลิตมะยงชิดพันธุ์ทูลเกล้าได้ คำสำคัญ : ถุงห่อ; คุณภาพผล; มะยงชิด Abstract ‘Toon Klaow’ Marian plum (Bouae burmanica Griff.) fruits were bagged at 30 days after anthesis (DAA) with different color plastic bags including black, red, green, white, light blue and yellow, compared with non-bagged. They were harvested at 70 DAA. Bagged fruits showed significant differences in increasing fruit weight, width, length and volume compared with non-bagged fruits. Fruits bagged with light blue plastic bags exhibited the highest fruit firmness. Fruits bagged with black plastic bags contained the highest TSS and TSS/TA, whereas those with green plastic bags were the lowest in % TA. Furthermore, the peel of fruits bagged with yellow plastic bags showed the highest lightness (L*) and redness (a*). Therefore the results indicate that bagging during fruit development on trees can improve fruits quality of ‘Toon Klaow’ Marian plum. Keywords: bagging material; fruit quality; Marian plum